Every death counts: measurement of maternal mortality via a census - Stanton Cynthia; Hobcraft John; Hill Kenneth; Kodjogbé Nicaise; Mapeta W.T.; Munene Francis; Naghavi Moshen; Rabeza Victor; Sisouphanthong Bounthavy; Campbell Oona (Bulletin of the World Health Organization, 2001)
Methods for measuring maternal mortality at national and subnational levels in the developing world lag far behind the demand for estimates. We evaluated use of the national population census as a means of measuring maternal mortality by assessing data from five countries (Benin, Islamic Republic of Iran, Lao People's Democratic Republic, Madagascar, and Zimbabwe) which identified maternal deaths in their censuses. Standard demographic methods were used to evaluate the completeness of reporting of adult female deaths and births in the year prior to the census. The results from these exercises were used to adjust the data. In four countries, the numbers of adult female deaths needed to be increased and three countries required upward adjustment of the numbers of recent births. The number of maternal deaths was increased by the same factor as that used for adult female deaths on the assumption that the proportion of adult female deaths due to maternal causes was correct. Age patterns of the various maternal mortality indicators were plausible and consistent with external sources of data for other populations. Our data suggest that under favourable conditions a national census is a feasible and promising approach for the measurement of maternal mortality. Moreover, use of the census circumvents several of the weaknesses of methods currently in use. However, it should also be noted that careful evaluation of the data and adjustment, if necessary, are essential. The public health community is urged to encourage governments to learn from the experience of these five countries and to place maternal mortality estimation in the hands of statistical agencies.